EFFECTIVENESS OF VIRTUAL REALITY THERAPY ON STRESS LEVEL AMONG UNDERGRADUATE NURSING STUDENTS (The Research of Medical Science Review, 2025)
Background: Stress is a major concern for nursing students globally, particularly those in post-RN programs, who balance full-time employment with academic responsibilities. This study determines the effectiveness of Virtual Reality Therapy, using a calming virtual river ride with nature sounds and visuals to reduce stress.Objective: The study aimed to determine the effectiveness of Virtual Reality Therapy in reducing stress levels among undergraduate nursing students.Materials and methods: A quasi-experimental pre-post and follow-up design was used to determine stress levels in 34 post-RN nursing students from Ziauddin University Faculty of Nursing and Midwifery Karachi, Pakistan, recruited through purposive sampling. Stress was measured using the Perceived Stress Scale (PSS-10) which consists of 10 statements before, immediately after, and two weeks post-intervention. The two-week intervention, part of a 4-month study (September 2024 to December 2024), aimed at reducing stress. Data were analyzed with the Statistical Package for the Social Sciences version 26.0. Descriptive statistics were applied to demographic variables, while the Friedman Test and Repeated Measures ANOVA determined Virtual Reality Therapy effectiveness. Bonferroni Pairwise Comparison checked time-point differences, and Chi-square was used for demographic associations.Results: The intervention-administered participants showed substantial reductions in stress levels from their initial 20.44±4.36 through the post-intervention assessment of 10.35±3.63 while follow-up results remained at 10.41±1.76 (p < 0.001). Initiative success reduced moderate stress impacts among students as 91.2% (n=31) reported moderate stress before intervention yet only 2.9% (n=1) students maintained this level of stress after the intervention while no participants experienced moderate or high stress at the follow-up examination. The study registered substantial stress decreases from pre-intervention until the first and second post-intervention follow-up periods. Stress levels after the intervention depended on employment status along with professional experience yet age, gender, year in study, marital status and living circumstances demonstrated no meaningful relationship with stress levels.Conclusion: Virtual Reality Therapy effectively reduced stress levels among undergraduate nursing students.